Численное моделирование распределения плотности электрических зарядов в фронтальных облаках - Белый, Т.А. (Геоінформатика, 2016)
Статья посвящена исследованию взаимодействия электрических и микрофизических процессов фронтальной облачности. Исследован механизм обратной связи между укрупнением частиц в облаке и ростом объемного заряда. Получены численные оценки распределения плотности зарядов фронтальных облаков для разных временных интервалов. Показано, что учет процессов коагуляции заметно перераспределяет объемный заряд в облаках. Численный эксперимент проведен с использованием трехмерной прогностической модели фронтальной облачности. Статтю присвячено дослідженню взаємодії електричних і мікрофізичних процесів фронтальної хмарності. Досліджено механізм зворотного зв’язку між укрупненням частинок у хмарі та зростанням об’ємного заряду. Отримано чисельні оцінки розподілу густини зарядів фронтальних хмар для різних часових інтервалів. Показано, що облік процесів коагуляції помітно перерозподіляє об’ємний заряд у хмарах. Чисельний експеримент проведено з використанням тривимірної прогностичної моделі фронтальної хмарності. Purpose. The increased interest in active influence on clouds and fogs has drawn considerable attention to the possibility of using electric forces for this purpose. In this context, the development of cloud numerical models and the study, based on these models, of various problems of cloud and precipitation formation, as well as electrical processes have become important both in research and application. Design/methodology/approach. A numerical experiment was conducted using atmosphere radio sounding field data on the basis of the three-dimensional prediction model of the frontal cloud cover. The model includes integr-differential equations with through consideration of thermodynamic and microphysical processes. Developed on the model physical principles, the methods for studying the microphysical and thermodynamic processes in the clouds are aimed at searching for feedback mechanisms between enlargement of the particles in the cloud and space charge growth. Findings. Within the framework of the frontal cloud cover 3D model, we investigated a feedback mechanism between enlargement of the particles in the cloud and space charge growth. We obtained numerical estimates of the distribution of the front cloud charges density in different time intervals. The numerical experiments showed the presence of broad areas of positive space charges in the upper part of the cloud cover, as well as the presence of the negative charges in the bottom part. The stratified nature of space charges cloud distribution is well consistent with studies by other authors. The positive charge area often exceeds the negative charge area. The negative charges exceed the positive ones by magnitude. The spatiotemporal distribution of the space charges is determined both by microphysical characteristics of the cloud cover and the evolution of the latter over time. Allowance for the coagulation processes noticeably redistributes the space charge in the clouds. Practical value/implications. The article deals with adaptation of the 3D non-stationary model of the frontal clouds with a detailed description of thermohydrodynamic and microphysical processes in order to estimate the electrical characteristics of the cloud cover. We carried out a series of numerical experiments to study the relationship of the microphysical characteristics and electrical processes in the clouds. We investigated a feedback mechanism between enlargement of the particles in clouds and growth of the space charge. Experimental studies of small-scale inhomogeneities of the space charge and measurements of the spectrum of individual drop size and charge in such inhomogeneities are of practical value for making a more accurate quantitative estimation of the electrical forces effect on non-electrical processes in clouds.